Milk Marketing and Dairy Value Chain Development in Nepal in Relation with Climate Resilience Effort in the Present Context - Sharma, B. (Nepalese Veterinary Journal, 2017)
Nepal is agricultural country with a special focus on dairy sub-sector. Almost 80% of milk in market, which have been produced by small holder farmers with a well- developed dairy value chain. Ministry of Livestock Development (MoLD) has given due importance for milk production providing support on feed and forage programs to the farmers as well as introducing crossbreeding programs to uplift the genetics of local cattle and buffaloes. By 2018, the country shall be self-sufficient in milk production, where the requirement of 91 lit of milk per person per year is expected to be achieved. Foot and Mouth Disease (FMD) emerges as a major health hazard in dairy sector apart from Hemorrhagic Septicemia (HS) and black quarter (BQ). The incidence of clinical and subclinical mastitis is still high in dairy pocket areas. Moreover, the seasonal fluctuation of milk production is hampering the growth of dairy sector. The need of product diversification and powder milk production are of immense important in long run to sustain dairy sub-sector in Nepal. MOLD has given priority for four pillars for livestock development namely animal feed, animal breeds, animal health and livestock marketing. That sector on balanced development program will lead to increase on milk, meat, eggs, nutrition, and food security in the nation.